a resposta da equação :
2x -3 + x = -5+ 4x
a) 2
b)3
c)4
d)5
Soluções para a tarefa
Respondido por
1
2x -3 + x = -5+ 4x = 2
Obs= explicação nas fotos.
Anexos:
![](https://pt-static.z-dn.net/files/d49/a474654092ad4929371d72bc9ba85526.jpg)
![](https://pt-static.z-dn.net/files/d0f/6c90f4ec7e2c2fbf0a9de1f9b5badcc7.jpg)
![](https://pt-static.z-dn.net/files/d86/de786819aeaba6105d1fb1617153027f.jpg)
![](https://pt-static.z-dn.net/files/d3e/2a43426328a34eb659fab2ebc4eab67c.jpg)
![](https://pt-static.z-dn.net/files/d95/d399d71f53e2a5998de2202b96bb41fc.jpg)
Respondido por
1
Resposta:
a) 2
Explicação passo-a-passo:
2x -3 + x = -5+ 4x
2x + x - 4x = - 5 + 3
- x = - 2 ( - 1) ⇒ vc mutiplica -x e -2 por -1
x = 2
Perguntas interessantes
História,
8 meses atrás
Física,
8 meses atrás
Geografia,
8 meses atrás
Ed. Física,
9 meses atrás
Biologia,
9 meses atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás